Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja Di Food And Beverage Department Premier Basko Hotel Padang - Desi Safiarti; Yuliana Yuliana (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
The purpose of this research is to explain the implementation of occupational safety and health management systems in the Premier Basko Hotel F&B product department both in terms of the determination of occupational safety and health policies, occupational safety and health planning, implementation of occupational safety and health plans, monitoring and evaluation of safety performance and occupational health, review and improvement of occupational safety and health. This research is a descriptive research with qualitative data, while the method used in this study is the survey method. The data in this study were collected through observation, documentation, and interviews with 6 informants. The conclusion of this research is that the overall implementation of the occupational safety and health management system in Premier Basko Hotel's food and beverage product department is still lacking, as seen in the many things that have not been implemented in the implementation of the occupational health and safety management system, as well as many procedures that are lacking in application.